Uninfluenced alpha-fetoprotein and treatment of liver primary carcinoma by lobaplatin in combination with 5-fluorouracil and doxorubicin via chemoembolization and transarterial chemoembolization - Chen, Yongpin; Li, Weibin; Yang, Qing; Chen, Liang; Zeng, Changjiang (Cellular and Molecular Biology, 2020)
Alpha-fetoprotein (AFP) is a protein encoded by the AFP gene and normally produced by the fetus. The purpose of this study is to investigate the efficacy of lobaplatin in combination with 5-fluorouracil (5-FU) and doxorubicin on AFP and treatment of primary carcinoma of the liver by transhepatic arterial chemotherapy and embolization (TACE). Patients with primary carcinoma of the liver who took the TACE for treatment were enrolled in this study and divided randomly into the research group and the control group. Patients in the research group adopted the TACE in combination with lobaplatin, while those in the control group took cisplatin instead in combination with TACE. We compared the baseline data, hepatic indicators before treatment and after 1 month of treatment, efficacy and the incidence rates of adverse events after TACE between two groups. Differences in the baseline data, including Child-pugh grade, type of liver cirrhosis, KPS scores and AFP showed no statistical significance (P >0.05). Before the treatment, we identified no significant differences in the comparison of ALT, AST, TBiL and ALB between two groups (P >0.05), while significant differences emerged after treatment (P <0.05). Also, efficacy comparison revealed the significant difference between the two groups (P <0.05). After TACE, patients in the research group reported 1 case of nausea, 1 of vomiting and 1 of necrotic absorption fever, and those in the control group reported 3 cases of nausea, 5 of vomiting and 4 of necrotic absorption fever, with a significant difference in comparison of the incidence rates (P <0.05). TACE is a promising strategy for the treatment of primary carcinoma of the liver, while lobaplatin, as the 3rd generation of anti-tumor platinum-based drugs, is less toxic than cisplatin, but excels in efficacy.